Experimental and Numerical Study of Rock Stratum Movement Characteristics in Longwall Mining - Wan-rong Liu (Shock and Vibration)
The roof fracture is the main cause of coal mine roof accidents. To analyze the law of movement and caving of the roof rock stratum, the roof subsidence displacement, rock stratum stress, and the rock stratum movement law were analyzed by using the methods of the particle discrete element and similar material simulation test. The results show that (1) as the working face advances, regular movement and subsidence appears in the roof rock strata, and the roof subsidence curve forms a typical “U” shape. As the coal seam continues to advance, the maximum subsidence displacement remains basically constant, and the subsidence displacement curves present an asymmetric flat-bottomed distribution. (2) After the coal seam is mined, the overburden forms an arched shape force chain, and the arched strong chain is the path of the overburden transmission force. The farther away from the coal seam, the smaller the stress concentration coefficient is, but it is still in a high stress area, and the stress concentration position moves toward the middle area of the goaf. The stress concentration in front of the coal wall is the source of force that forms the abutment pressure. (3) Above the coal wall towards the goaf, a stepped fracture was formed in the roof rock stratum. The periodic fracture of the rock stratum is the main cause of the periodic weighting of the working face. Understanding the laws of rock movement and stress distribution is of great significance for guiding engineering practice and preventing the roof accidents.